In situ conservation of Populus nigra - Lefèvre, F.; Barsoum, N.; Heinze, B.; Kajba, D.; Rotach, P.; Vries, S.M.G. de; Turok, J.; European Forest Genetic Resources Programme (2001)
P. nigra is a typical pioneer tree species of the riparian forest ecosystem. Therefore, the in situ gene conservation strategies and methods developed for other forest tree species are not always suitable. In fact, successful in situ conservation strategies for black poplar need to consider the current status and management of existing populations as well as the physical dynamics of the natural habitat formed by the river. Furthermore, conservation relies heavily on the potential to restore entire floodplain ecosystems, as well as the development of appropriate strategies for the management of restored sites. These factors not only determine the objectives of designated in situ conservation units, but also the methods and costs of the approach that is ultimately adopted.